PERSEPSI MASYARAKAT TERHADAP PENGEMBANGAN INDUSTRI RUMAH PANGGUNG DI DESA TOMBASIAN ATAS, KECAMATAN KAWANGKOAN BARAT, KABUPATEN MINAHASA - Meifa Priscilia Lindaan; Ventje V. Rantung; Melsje Y. Memah (AGRI-SOSIOEKONOMI, 2016)
This study aims to analyze Public Perceptions of The Industry Development Stage House in the Village of the District Tombasian Kawangkoan Barat. The analysis used in this research is by using a Likert Scale analysis. Data collection was conducted over four months, since February until April ranging from preparation of research reports. The research location is housed in the Village Tombasian Kawangkoan Barat District of Minahasa. This study uses primary data obtained directly through a questionnaire to the villagers of the District Tombasian Kawangkoan. Secondary data obtained through the government in the village Tombasian. Sampling using simple random sampling metod, wherr all members have the same population was selected as a representative sample of the population. To determine the public perception then used the likert scale analysis. The results showed that a high perception of the Industrial Development Society House Stage in the Village District of Kawangkoan Barat Tombasian, seen from three indicators of responses/opinions, knowledge, and attitudes.